KEEPING JUSTICE (LARGELY) OUT OF CHARITY: PLURALISM AND THE DIVISION OF LABOR BETWEEN CHARITABLE ORGANIZATIONS AND THE STATE. (December 2020) - Halliday, Daniel; Harding, Matthew
Abstract: Justice can be pursued by the state, or through voluntary charity. This paper seeks to contribute to the debate about the appropriate division of labor between government and charitable agencies by developing a positive account of the charity sector's moral foundations. The account given here is grounded in a legal conception of charity, as a set of subsidies and privileges designed to cultivate a wide variety of activities aimed at enhancing civic virtue and autonomy. Among other things, this implies that a charity sector oriented largely around the pursuit of justice will come at a moral cost to a liberal society, at least when the state is in a position to take the greater share of the responsibility. So, a positive account of charity provides at least a pro tanto reason for preferring a division of labor in which the state takes a greater share of the responsibility for pursuing justice. As well as developing and defending this conception in its own right, we apply it in offering some criticisms and enhancements of existing views about the division of labor.